IMMU-17. TARGETING GLIOBLASTOMA WITH DNAM-1-BASED CHIMERIC ANTIGEN RECEPTOR (CAR) T CELLS. (11th November 2019) - Weiss, Tobias; Meister, Hanna; Weller, Michael; Sentman, Charles; Roth, Patrick
Abstract: BACKGROUND: Genetically engineered T cells that express a chimeric antigen receptor (CAR) have shown powerful anti-tumor activity in extracranial malignancies. This concept is now also being explored against glioblastoma. However, many single target antigens used for CAR cell therapy are non-homogeneously expressed. We assessed the therapeutic potential of CAR T cells targeting 2 antigens which are homogeneously expressed by glioma cells which reduces the probability of tumor immune escape due to antigen loss. METHODS: We analyzed the expression of CD112 and CD155, which are ligands to the activating immune cell receptor DNAX Accessory Molecule-1 (DNAM-1), in a panel of mouse and human glioma cell lines as well as in human glioblastoma samples and generated glioma cells with a CD112 or CD155 knock-out. To exploit the specific binding properties of DNAM-1, we generated first or second-generation CAR T cells that use DNAM-1 as an antigen-binding domain and investigated their anti-tumor activity in vitro and in vivo using syngeneic orthotopic mouse glioma models. RESULTS: CD112 and CD155 are homogeneously expressed in mouse and human glioma cell lines as well as human glioblastoma tissue specimens. CRISPR/Cas9-mediated knock-out of CD112 or CD155 affected the migration of glioma cells, but had no impact on the proliferation or susceptibility to irradiation or temozolomide. DNAM-1-based CAR T cells exerted high cytolytic activity and secretion of various effector cytokines in vitro . Upon intravenous administration, DNAM-1-based CAR T cells did not exert significant toxicity, homed to the tumor site in the brain and prolonged the survival of orthotopic glioma-bearing mice with durable anti-tumor responses in a fraction of mice. CONCLUSION: CD112 and CD155 represent attractive targets for glioma immunotherapy using genetically engineered immune cells. Based on the data obtained from our preclincal assessment of DNAM-1-based CAR T cells, this immunotherapeutic strategy might also be explored in human glioma patients.